2020
DOI: 10.1016/j.jmbbm.2020.104078
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired approaches to toughen calcium phosphate-based ceramics for bone repair.

Abstract: Highlights:• Bone has a complex multi-level hierarchical organisation. This structural organisation is key for its outstanding properties. • Artificial calcium phosphate ceramics (CPCs) are promising for achieving the set of mechanical and biological requirements for use as bone implants. • At individual lengthscales, methods have been developed to control crystal phases, microscale porosity and macroscopic geometry but the CPCs produced remain intrinsically brittle. • Inspired by the organisation of bones and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 156 publications
2
20
0
1
Order By: Relevance
“…Studies revealed that, during the thermal treatment, Gr may prevent the successful coalescence of all ceramic particles, leading to an open porosity and a less-densified microstructure. However, the occurrence of a secondary porosity with bone-like pore sizes was shown as beneficial for cell adhesion and proliferation, fluid transportation, and/or nerve accommodation [ 8 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Studies revealed that, during the thermal treatment, Gr may prevent the successful coalescence of all ceramic particles, leading to an open porosity and a less-densified microstructure. However, the occurrence of a secondary porosity with bone-like pore sizes was shown as beneficial for cell adhesion and proliferation, fluid transportation, and/or nerve accommodation [ 8 ].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the practicality of Lu fiber use as porogen template is restricted by the concomitant addition of the Gr agent (as mechanical reinforcement agent) up to maximum 0.50 wt.% when the sintering program is conducted in nitrogen ambient. Other than that, the proposed 3D geometries comply with the tortuosity and interconnectivity degree, the pore and channel sizes (around 100–500 μm) [ 5 , 8 , 71 ], and can stand as precursor arrays for future osteogenesis when implemented in various bone healing applications. Since the mechanical features are also of great importance for favorable in vivo performance of the scaffolds, a compromise can be attained with respect to the porosity degree [ 32 ], by modulating the amounts of Lu fibers and/or Gr agents.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations